Integration of golf practise and strength and conditioning in golf: Insights from professional golf coaches - Bliss, A.; Langdown, B. (International Journal of Sports Science & Coaching, 2024)
Strength and conditioning (S&C) interventions for golfers consistently demonstrate improvements in performance metrics such as clubhead speed. Golfers typically employ Professional Golfers` Association (PGA) coaches to support technical and tactical development. These coaches need to ensure golfers balance S&C training alongside competitions and technical golf practise, although no empirical data exist that demonstrates how this integration occurs practically. This study aimed to investigate the perceptions and practises of PGA Professional golf coaches and how S&C is integrated into the golf year. Forty-three (male = 35; female = 8) PGA coaches completed a mixed-methods survey with questions on themes such as coaching approach, perceptions of S&C, annual planning and goal setting. Results show that formal planning processes are highly variable or absent. The majority (n = 29; 70.7%) of PGA coaches stated they worked with an S&C coach and see the role of the S&C coach to support golfers with their input. However, when planning the season, 63.4% (n = 26) of coaches do so without input from the S&C coach. These and other related disconnects between desire for S&C intervention and inclusion of the S&C coach in planning processes were evident throughout survey responses. There may be subsequent risks of conflict or misunderstanding between PGA coach, S&C coach and golfer. It is recommended golf coaches, golfers and S&C coaches work collaboratively as a multidisciplinary support team to ensure coordinated golfer support is obtained.